(untitled) (Orinoquia, 2017)
The TiO2 /ZnO nanofibers prepared by the calcination of polyvinyl acetate of precursor fibers, titanium isopropoxide and nano zinc powder produced by the electrospinning technique were studied. The structure and morphology of TiO2 /ZnO nanofibers and precursor fibers were characterized by Scanning Electron Microscopy (SEM), Field Emission Scanning Electron Microscopy coupled to Energy Dispersive X-ray spectroscopy (FESEM-EDS), Fourier Transform Infrared Spectroscopy (FTIR) and XRD (X Ray Diffraction). XRD analysis displayed crystalline structures of titanium oxides (anatase) and zinc (hexagonal wurzite), after calcining the precursor fibers at 500 °C. SEM microphotographs display that both precursor fibers and nanofibers form uniform networks and good morphology. These titanium dioxide / zinc oxide nanofibers get good surface area and appropriate 200 nm diameters which could potentially be applied in the renewable energy field, particularly for solar cells manufacturing.